The growth of Typhonium flagelliforme treated with different levels of thidiazuron and N⁶ benzylaminopurine - Sunoto @ Hj. Faisal, Vajidah (2012)
Since it has known as herbal therapies for cancer treatment, the demand for Typhonium flagelliforme plant is high. Shortage of high quality planting materials has limited the supply of this plant. Through in vitro technique, mass multiplication of rodent tuber has been achieved. Thus a study was conducted at Cell Biology and Genetics Laboratory, Department of Agriculture Technology, Faculty of Agriculture. An experiment was conducted using two different cytokinins, BAP and TDZ in New Dogashima Medium at various levels of concentrations for this study. The objectives of this study are to study the effect of different concentrations of BAP and TDZ on the multiplication of T. flagelliforme on modified NDM medium and to determine the best concentration of hormones used for mass propagation of T. flagelliforme. The explant used was very small portion of tuber. A series of explant sterilizations were conducted before undergo culturing process. Twelve treatments used are BAP and TDZ with 0, 0.25, 0.5, 1, 3, and 5 mg/L respectively, added with 0.1 mg/L NAA to induce root growth for complete growth of individual plant. The explants were subcultured onto similar fresh media every 2 weeks. Parameters that were recorded include fresh weight of culture (g), explant height (cm), number of shoot(s) and root(s) per explant. Percent of contamination and dead of explant were also recorded. This study was conducted using Complete Randomized Design (CRD) and data were analyzed using the Analysis of Variance (ANOVA) and Duncan Multiple Range Test (DMRT) was employed for comparison between means. After several weeks of culture, the results showed that there were significant differences on the growth of explants among all the treatments.